Correlation of senses of word society in a dictionary and discourse - Жовнір, Марина Миколаївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The article deals with the discursive senses of word society and its corresponding sense in the dictionary. The article considers the problem of lexical combinability as an indicator of ideal correlation between the discursive and corresponding dictionary meanings. The analysis is carried out on the example of modern, classic fiction literature and mass media texts. The paper presents the classification and description of the contextual meaning of the word society. The author has divided all contexts into traditional and unconventional (modern).The semantic transformation of secularism, as a specific phenomenon of the Ukrainian culture was traced. Reality is dynamic, so various social, historical and cultural processes assist appearance of new lexemes, their senses and lexicographic representations. At the beginning of XXI century the elite way of life became very popular in our country. As a result of changing lifestyles word combinations with component society has been spread and quickly became popular. The novelty of investigation lies in presentation of noticeable differences between present and classic interpretation of this word.